Optogenetic demonstration of the involvement of SMA-negative mural cells in the regulation of cerebral blood flow - Iba, Chisato; Abe, Yoshifumi; Tanaka, Kenji F. (Frontiers in Physiology, 2023)
Mural cells are critical components of the cerebral vasculature. They are categorized into three primary subsets: arteriole smooth muscle cells (aSMCs), pericytes (PCs) and venule smooth muscle cells (vSMCs). It is well known that aSMCs can directly regulate cerebral blood flow (CBF) with their own contraction and dilation mechanisms. On the other hand, the direct involvement of PCs or vSMCs in CBF regulation is controversial. This ambiguity is largely due to the lack of specifically manipulable tools to isolate their function. To address this issue, we employed a set-subtraction approach by using a combination of tTA-mediated gene induction and Cre-mediated gene excision. We developed transgenic mice expressing optical actuators, channelrhodopsin-2 (ChR2) and photoactivated adenylyl cyclase (PAC) in smooth muscle actin (SMA)-negative mural cells that lack the machinery for SMA-mediated vasoregulation. Using these mouse models, we assessed CBF alterations in response to optical stimulation using laser Doppler techniques. Our results showed that optical stimulation induced notable CBF changes in both models. This study provides evidence for the potential regulatory role of PCs and vSMCs in cerebral hemodynamics and introduces powerful tools to specifically manipulate these cell types in vascular neurobiology.